Effects of early clozapine treatment on remission rates in acute schizophrenia (the EARLY trial): protocol of a randomized-controlled multicentric trial - Wagner, Elias Maximilian; Strube, Wolfgang; Görlitz, Thomas; Aksar, Aslihan; Bauer, Ingrid; Campana, Mattia; Moussiopoulou, Joanna; Hapfelmeier, Alexander; Wagner, Petra; Egert-Schwender, Silvia; Bittner, Robert; Eckstein, Kathrin; et al. (Pharmacopsychiatry, 2023)
Background: Quick symptomatic remission after the onset of psychotic symptoms is critical in schizophrenia treatment, determining the subsequent disease course and recovery. In this context, only every second patient with acute schizophrenia achieves symptomatic remission within three months of initiating antipsychotic treatment. The potential indication extension of clozapine—the most effective antipsychotic—to be introduced at an earlier stage (before treatment-resistance) is supported by several lines of evidence, but respective clinical trials are lacking. Methods: Two hundred-twenty patients with acute non-treatment-resistant schizophrenia will be randomized in this double-blind, 8-week parallel-group multicentric trial to either clozapine or olanzapine. The primary endpoint is the number of patients in symptomatic remission at the end of week 8 according to international consensus criteria (‘Andreasen criteria’). Secondary endpoints and other assessments comprise a comprehensive safety assessment (i. e., myocarditis screening), changes in psychopathology, global functioning, cognition, affective symptoms and quality of life, and patients’ and relatives’ views on treatment. Discussion:This multicentre trial aims to examine whether clozapine is more effective than a highly effective second-generation antipsychotics (SGAs), olanzapine, in acute schizophrenia patients who do not meet the criteria for treatment-naïve or treatment-resistant schizophrenia. Increasing the likelihood to achieve symptomatic remission in acute schizophrenia can improve the overall outcome, reduce disease-associated burden and potentially prevent mid- and long-term disease chronicity.
Gesehen am 14.08.2024